Systematic Ocular Phenotyping of Knockout Mouse Lines Identifies Genes Associated With Age-Related Corneal Dystrophies - Briere, Andrew; Vo, Peter; Yang, Benjamin; Adams, David; Amano, Takanori; Amarie, Oana; Berberovic, Zorana; Bower, Lynette; Brown, Steve D M; Burrill, Samantha; Cho, Soo Young; Clementson-Mobbs, Sharon; et al. (Investigative ophthalmology & visual science, 2025)
PURPOSE: This study investigates genes contributing to late-adult corneal dystrophies (LACDs) in aged mice, with potential implications for late-onset corneal dystrophies (CDs) in humans. METHODS: The International Mouse Phenotyping Consortium (IMPC) database, containing data from 8901 knockout mouse lines, was filtered to include late-adult mice (49+ weeks) with significant (P < 0.0001) CD phenotypes. Candidate genes were mapped to human orthologs using the Mouse Genome Informatics group, with expression analyzed via PLAE and a literature review for prior CD associations. Comparative analyses of LACD genes from IMPC and established human CD genes from IC3D included protein interactions (STRING), biological processes (PANTHER), and molecular pathways (KEGG). RESULTS: Analysis identified 14 genes linked to late-adult abnormal corneal phenotypes. Of these, 2 genes were previously associated with CDs in humans, while 12 were novel. Seven of the 14 genes (50%) were expressed in the human cornea based on single-cell transcriptomics. Protein-protein interactions via STRING showed several significant interactions with known human CD genes. PANTHER analysis identified six biological processes shared with established human CD genes. Two genes (Rgs2 and Galnt9) were involved in pathways related to human corneal diseases, including cGMP-PKG signaling, mucin-type O-glycan biosynthesis, and oxytocin signaling. Other candidates were implicated in pathways such as pluripotency of stem cells, MAPK signaling, WNT signaling, actin cytoskeleton regulation, and cellular senescence. CONCLUSIONS: This study identified 14 genes linked to LACD in knockout mice, 12 of which are novel in corneal biology. These genes may serve as potential therapeutic targets for treating corneal diseases in aging human populations.
Keywords: Corneal Dystrophies, Hereditary; Disease Models, Animal; stárnutí; myši; myši knockoutované; modely nemocí na zvířatech; fenotyp; Aging; Phenotype; Animals; lidé; Mice, Knockout; dědičné dystrofie rohovky; Mice; Humans; zvířata